CIDAT: Collection and dissemination of knowledge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Belgium has accumulated considerable experience in tropical agriculture over the years. This is the fruit of work carried out in research centres in its former African colonies and in other parts of the world where Belgian experts have been...